Unexpected Inflation, Real Wages, and Employment Determination in Union Contracts - Card, David (American Economic Review, 1990)
This paper examines the effect of nominal contracting provisions on employment determination in union contracts. In most contracts the nominal wage rate is wholly or partially predetermined. Real wage rates therefore contain unanticipated components that reflect unexpected price changes and the degree of indexation. The empirical analysis, based on a large sample of indexed and nonindexed contracts, suggests that unexpected real wage changes are associated with systematic employment responses in the opposite direction. I conclude that nominal contracting provisions play a potentially important role in the cyclical properties and persistence of employment movements in the union sector.